Marine Strategy of the Guanacaste Conservation Area - Méndez, Guiselle (2005)
The  sustainability  of  the  coastal-marine  resources requieres integral work, from governmental policies to local actions. The main participants are undoubtley the locals who must be directly involved and who in conjuction have to analyze the troublesome situations and search for alternatives. The article summarizes the work of the Area de Conservación Guanacaste (ACG) (Guanacaste Conservation Area), which is the responsible  entity  that  manages  the  environment in the norteast of Guanacaste. The ACG has tried to search for a marine strategy that increases the development of the coastal-marine protected area. Among  the  first  challenges  of  the  ACG  are:  the environmental  education,  the  identification  of productive activities, the complete analysis of the social, political, and environmental problems as well as the interinstitutional coordination. These challenges have been worked along with the community in pursue of an effective management of the marine resources of this protected wild reserve.